Blockchain-Enabled Smart Agricultural Knowledge Discovery System using Edge Computing - Sakthi, U; DafniRose, J (Procedia computer science, 2022)
Blockchain empowered agricultural knowledge discovery system provides the secured environment for the people to store and exchange agricultural data. The integration of the Internet of Things (IoT), blockchain technology, and edge computing supports the agricultural fields to increase crop productivity and reduce the usage of natural resources. The smart decision support system provides efficient data management to the farmer to make the best decision to increase crop productivity and profit. In the agriculture field, different sensors and devices collect different data about the land then it can be sent to the server in the cloud environment. These data are highly sensitive and need to be securely stored and protected against unauthorized access. The farmers can communicate with the intelligent decision support system using the mobile app and web applications to get information about the land from domain experts. The proposed system used blockchain technology to provide privacy, security, easy accessibility, and availability of information to the people to use natural resources effectively and reduce the effect of soil and water pollution by using pesticides and fertilizer based on data stored in the knowledge base. We have implemented a knowledge discovery system using the platform hyperledger for efficient storage and sharing of sensor data which provides security and data privacy. Precision agriculture with IoT and Edge computing allows people and devices to be connected anywhere, anytime in a smart cloud environment to provide intelligent service to the farmers.